2019
DOI: 10.1177/0272684x19873787
|View full text |Cite
|
Sign up to set email alerts
|

Brief Relaxation Training for the Prevention of Stress-Related Difficulties: A Pilot Study

Abstract: The present study piloted a brief, single-session behavioral intervention to prevent stress-related illnesses in college students. Participants were recruited at a large public university ( N =  213). A total of 132 participants completed in-person research sessions and were randomly assigned to one of three conditions (two control and one intervention), and another 81 participants completed measures online (online control) without any face-to-face contact. The intervention consisted of brief, one-on-one diaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…After 20 days of intervention, it was found that the pulmonary function indexes FVC, FEV1, PaO 2 , and SpO 2 of patients with type II respiratory failure increased significantly after abdominal breathing training, while PaCO 2 decreased significantly [37]. Other scholars believe that abdominal breathing training can improve the enthusiasm and compliance of COPD patients to participate in treatment, shorten the length of stay of patients, and improve their quality of life [38]. In addition, based on routine treatment, Chinese scholars studied the effect of pike abdominal breathing on the respiratory function of patients undergoing laparotomy and compared the pulmonary function indexes with those before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…After 20 days of intervention, it was found that the pulmonary function indexes FVC, FEV1, PaO 2 , and SpO 2 of patients with type II respiratory failure increased significantly after abdominal breathing training, while PaCO 2 decreased significantly [37]. Other scholars believe that abdominal breathing training can improve the enthusiasm and compliance of COPD patients to participate in treatment, shorten the length of stay of patients, and improve their quality of life [38]. In addition, based on routine treatment, Chinese scholars studied the effect of pike abdominal breathing on the respiratory function of patients undergoing laparotomy and compared the pulmonary function indexes with those before treatment.…”
Section: Discussionmentioning
confidence: 99%